Fundraising, celebrations and classroom rewards are substantial sources of unhealthy foods and beverages on public school campuses - Caparosa, Susan L.; Shordon, Maggie; Santos, Asherlev T.; Pomichowski, Magdalena E.; Dzewaltowski, David A.; Coleman, Karen J. (My University, 2014)
Objective: The emphasis in school nutrition policy has been on vending and competitive items. Our study was designed to characterize and quantify the amount and source of other foods and beverages on school campuses. Design: A cross-sectional observational study was conducted using a specially designed objective nutrition observation system. Setting: One low-income school district in southern California with six elementary and two middle schools. Subjects: Data were not collected from individual children. A total of 4033 students, 42 % of whom were Hispanic/Latino, 26 % African American and 21 % non-Hispanic white, were observed across school settings. Results: Data were collected continuously from 9 January 2008 to 16 June 2010. Healthy foods had, per serving, total energy ≤732 kJ (≤175 kcal), total fat content ≤35 %, total saturated fat ≤10 %, sugar less ≤15 g, sodium <200 mg and trans-fat ≤0·5 g. Healthy beverages were only 100 % juice or water, and unflavoured non-fat, 1 %, 2 % milk and soya or rice milk. The system had high inter-rater reliability (r = 0·78 to 0·99), percentage agreement (83 % to 100 %) and test–retest reliability (r = 0·81 to 0·98). Significantly more unhealthy foods and beverages than healthy items were observed on all campuses (P < 0·001). An average of 1·26 (sd 0·46) items per student per week was found with an average of 0·86 (sd 0·34) unhealthy items per child per week. Conclusions: There were substantial amounts of unhealthy foods and beverages brought onto campuses for classroom rewards, celebrations and fundraising that should be targeted for intervention.
Keywords: Child obesity; School health; Nutrition; Underserved; Minority health